Novel 3,5- bis(fluorobenzylidene)piperidin-4-ones as regulators of wheat growth : Fluorine-containing piperidin-4-ones, stimulants of wheat growth, retardant (International Journal of Biology and Chemistry, 2021)
In plant growing, the practical value of growth regulators is determined by the ability to significantly accelerate the development and increase the productivity of most agricultural crops.One of the most important tasks of the technology of wheat production is a target search for novel effective growth regulators. To determine the effect of the presence of fluoride in a molecule with the binding fragment of N-(2-ethoxyethyl)piperidine, as well as the substitution of ethoxyethyl substituent at nitrogen of piperidine cycle on benzyl it had been synthesized fluorine-containing piperidines. It turned out that the pre-treatment of seeds of spring wheat varieties Kazakhstanskaya-10, Severyanka and Miras with 0.01% solutions of 3,5-bis (fluorobenzylidene)piperidin-4-ones  as complexes with β–cyclodextrin regulates the effect on germination and development. Dienone with ethoxyethyl substitute at nitrogen of piperidine cycle stimulates growth, and its N-benzyl analogue is a retardant.Target 3,5-bis(fluorarylidene)-4-piperidones were synthesized via the conditions of the Kleisen-Schmidt reaction by the interaction of piperidine-4-ones with fluorobenzaldehyde in ethanol in the presence of sodium hydroxide with a yield of 40.8-50.9%: Synthesized dienones are crystalline substances, limited soluble in water.